KEARIFAN LOKAL DALAM PEMBENTUKAN DAERAH OTONOMI BARU DI ERA OTONOMI DAERAH (STUDI KASUS: KEARIFAN LOKAL DI DAERAH APAU KAYAN KABUPATEN MALINAU) - Muhammad Risal (Jurnal Administrative Reform, 2017)
This research is aim to explain how local wisdom could play an important role in shaping and forming a new autonomous region (DOB). It is shown that local wisdom in Apau Kayan is very influential in social, economic and cultural life of the people. Apart from that, this can be viewed as the implementation of assymetric decentralization where local government is given a broader authority by Central Government to regulate their own region according to existing local wisdom. In this sense, it is perceived as an effective way of incorporating local wisdom as an integral part of local development.